Educational Perspectives on the Struggle of Prophet Muhammad SAW: A Historiographic Study Based on J. Suyuthi Pulungan's Works - Fatmawati Fatmawati; Duski Ibrahim; Endang Rochmiatun (STAI Hubbulwathan Duri, 2025)
This study investigates the historiographical portrayal of the Prophet Muhammad’s (SAW) struggle during the Meccan and Medinan phases, as documented in History of Islamic Civilization by Prof. Dr. J. Suyuthi Pulungan, MA. The research aims to trace and critically analyze the historical narrative presented in the text, particularly concerning the early Islamic struggle and the development of Islamic civilization. A qualitative, non-interactive library research design was employed, utilizing historical methods. Data analysis involved content and comparative analysis to interpret textual representations and construct a historiographical account based on the selected work. Findings indicate that in the Meccan phase, the book omits several pivotal events in the Prophet’s early da'wah efforts, including the reception of revelation, phases of secret and public preaching, the Isra' Mi'raj, and the concealment in the Cave of Tsur. In the Medinan phase, while the establishment of the Nabawi Mosque is mentioned as a central development in Islamic civilization, the economic system during this period is notably absent. The study reveals both the strengths and limitations in the historiographical construction of Islamic history within this text. It emphasizes the need for a more comprehensive inclusion of key events and socio-political aspects in future historiographical works to provide a fuller understanding of the Prophet Muhammad’s (SAW) legacy. Further research is recommended to compare additional classical and contemporary historiographies for a more holistic analysis.